Comparison of externally and internally guided dance movement to address mobility, cognition, and psychosocial function in people with Parkinson’s disease and freezing of gait: a case series - Abraham, Amit; Hart, Ariel; Bozzorg, Ariyana; Pothineni, Suraj; Wolf, Steven L.; Schuh, Kersey; Caughlan, Molly; Parker, Jelani; Blackwell, Amanda; Tharp Cianflona, Megan; Asker, Courtney; Prusin, Todd; et al. (Frontiers in Aging Neuroscience, 2024)
Objective The aim of this study is to explore the impact of internally guided (IG) versus externally guided (EG) adapted tango (AT) dance training (i.e., dancing the IG “Leader” role or the EG “Follower” role), on motor and non-motor functions in individuals with Parkinson’s disease and freezing of gait (PD-FOG). The “Leader” role, a proxy for IG movements, conveys direction, timing, and amplitude of steps with tactile cues. The “Follower” role, a proxy for EG movements, detects and responds to the leader’s tactile cues. Case description Six participants were randomly assigned to the IG (“Leader”) or EG (“Follower”) roles for 20, 90-min AT lessons over 12 weeks. Participants were assessed for PD-specific and non-PD-specific functions before and twice after the end of the 12-week intervention, at 1-week and 1-month post-intervention. Results EG participants improved and/or maintained performance on more outcomes across all domains than IG participants. Five participants improved in PD motor symptoms, dynamic gait, global cognitive function, and the FOG Questionnaire immediately or 1 month after intervention. All participants expressed positive attitudes toward the intervention, including improvements in walking, balance, and endurance. Conclusion AT training in the follower role may benefit individuals with PD-FOG to a greater extent compared to the leader role. Impact This case series study could inform additional research with the goal of enhancing physical therapy or music-based therapy approaches for addressing PD-FOG.